(untitled) (ESMAT Magazine, 2024)
This article seeks to understand the process of transition from public and collective possession and property to private possession and property. To this end, the objectives are the historical description of the occupation of Brazilian territory and the construction of the normative set of possession and property as a right in the legal system. The approach used is deductive. The technique used is an interdisciplinary theoretical-bibliographical review, supported by legal historiography in order to analyze the social history of possession and property in the Brazilian legal system, as well as a legal-normative approach with an analytical-critical focus. In the end, it is concluded that the concept of possession and property, initially based on a collective dimension, according to the first land regime (sesmarias), was transformed into a right to private possession and property, typical of the economic market. However, this view is exclusionary because it disregards other collective forms of land use.